Glycomacropeptide Attenuates Inflammation, Pruritus, and Th2 Response Associated with Atopic Dermatitis Induced by 2, 4-Dinitrochlorobenzene in Rat. (7th February 2017) - Muñoz, Fabiola Carolina; Cervantes, Maritza Montserrat; Cervantes-García, Daniel; Jiménez, Mariela; Ventura-Juárez, Javier; Salinas, Eva
Abstract : Atopic dermatitis (AD) is one of the most common skin diseases, whose incidence is increasing in industrialized countries. The epicutaneous application of a hapten, such as 2, 4-dinitrochlorobenzene (DNCB), evokes an experimental murine AD-like reaction. Glycomacropeptide (GMP) is a dairy bioactive peptide derived from hydrolysis of κ -casein by chymosin action. It has anti-inflammatory, prebiotic, and immunomodulatory effects. The present study was aimed to investigate the effect of GMP administration on DNCB-induced AD in rats. The severity of inflammatory process, pruritus, production of cytokines, and total immunoglobulin E (IgE) content were measured, and the histopathological features were analyzed. GMP reduced the intensity of inflammatory process and edema of DNCB-induced dermatitis, with a significant decrease in eosinophils recruitment and mast cells hyperplasia. In addition GMP suppressed the serum levels of total IgE and IL-4, IL-5, and IL-13 expression in AD-lesions. Besides, the levels of IL-10 were significantly increased. Remarkably, GMP administration before AD-induction abolished pruritus in dermatitis-like reactions in the rats. Taken together, these results indicate that GMP has an inhibitory effect on AD by downregulating Th2 dominant immune response, suggesting GMP as a potential effective alternative therapy for the prevention and management of AD.